(untitled) (Medico Legal Update, 2019)
College students majoring in health care who will lead the future health community studied consciousness of sex, attitudes toward homosexuality and acceptance of homosexuality. From March 5 to 15, 2018, the program was conducted for students majoring in health education who are attending a four-year university located in South Chungcheong Province. First, the purpose and procedure of the study were described and agreed upon by students, and the results of the survey were analyzed using the SPSS statistics program. Research shows that sexual consciousness, attitudes toward homosexuality and acceptance of homosexuality differed a lot according to demographic characteristics. Correlations have shown that students who are openminded about sex have a positive attitude toward homosexuality and have high acceptance of homosexuality. A proper education is needed based on the results of the study, as the values and behaviors of incorrect sex can lead to a lot of confusion and physical damage.